Modeling and Optimization Teacher Work Innovation : An Empirical Study Using POP-SDM Approach on Vocational Teachers of Private Vocational Schools in Depok - Nelfuad, Nelfuad; Hardhienata, Soewarto; Setyaningsih, Sri (AGUSPATI Research Institute, 2021)
The research aims to find ways and strategies to improve teacher work innovation by analyzing the influence of other variables that influence it. Reasearch using the Modeling and Optimization of Resource Management Approach (POP-SDM). At the initial stage Qualitative exploratory research was conducted on 7 principals of SMK to find variables that affect teacher work innovation. Based on the dominant variables found, a constellation model of research was built through theoretical studies and expert judgment. Furthermore, the research constellation model was tested through quantitative research using SEM-PLS on 157 vocational teachers of SMK. The sub structural models tested were: 1) The direct influence of proactive personality, adversity quotient, organizational support, technological pedagogical content knowledge, and work motivation on teacher work innovation; 2) The direct influence of proactive personality and adversity quotient on technological pedagogical content knowledge; 3) The direct influence of organizational support on work motivation.The study found: 1) Teacher work innovation can be explained by the influence of proactive personality, adversity quotient, organizational support, technological pedagogical content knowledge and work motivation, R2 = 0.753 (75.3%) with the structural equation Y = 0.514X1 + 0.259X2 + 0.579X3 + 0.274X4 + 0.226X5 + Îµ0.497; 2) technological pedagogical content knowledge can be explained by the influence of proactive personality and adversity quotient, R2 = 0.355 (35.5%) with structural equation X4 = 0.408X1 + 0.303X2 + Îµ0.803; 3) Work motivation can be explained by the influence of organizational support, R2 = 0.417 (41.7%) with the structural equation X4 = 0.408X1 + 0.303X2 + Îµ0.803. The value of Q2 = 0.734 indicates the model has a GoF of 73%. (Good category). The results of hypothesis testing also concluded that the variables of technological pedagogical content knowledge and work motivation were not effective as intervening variables. Thus, the improvement of teacher work innovation is more effectively carried out directly through strengthening proactive personality, adversity quotient, organizational support, technological pedagogical content knowledge and work motivation.Sitorem's analysis concluded that organizational support variables and knowledge of pedagogical content had a major influence on teacher work innovation. As a follow-up to the research results, strengthening the indicators that are still weak in these two variables is a priority to be improved immediately.